2014
DOI: 10.1007/s00231-014-1461-7
|View full text |Cite
|
Sign up to set email alerts
|

Bubble departure size in flow boiling

Abstract: HHeight from the beginning of heated portion of rod (m) JaJacob number k w Dimensionless bubble contact diameter L Perimeter of heated rod (m) n Constant p Pressure (Pa) q w Heat flux (kW/m 2 ) r Bubble radius (m or mm) Re b Bubble Reynolds number t Time (s) T Temperature (°C) U b Bubble velocity (m/s) U(x) Liquid velocity profile near wall (m/s) V b Bubble volume (m 3 ) u l Mean velocity of two phase (m/s) u* Friction velocity (m/s) X Vapor quality Greek symbols α Advancing contact angle β Receding contact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“… Proposed correlation by Prodanovic et al [24] was modified and adapted for predicting bubbles departure diameter and nucleation frequencies in U-shaped channels through adding Dean number as a new factor, which considers the influence of the curved geometry and subsequently, radial pressure gradient on bubbles characteristics. Ghunther [19] 0.32-1.02 0.8-3 Tolubinsky and Kostanchuk [20] 0.47-1.24 1.2 Ünal [5] 0.11-0.18 Klausner et al [22] 0.1-0.65 Thorncroft et al [23] 0.09-0.25 0.12-45 1-1.8 17-30 Prodanovic et al [24] 0.3-2.68 0.37-2.86 0.41-9.5 0.81-18.6 Situ et al [42] 0.145-0.6 Cho et al [1] 0.46-0.56 0.55-0.9 Chu et al [9] 0.51-1.71 77-300 Euh et al [41] 20-900 Zou and Jones [27] 0.15-0.45 Sugrue et al [3] 0.22-0.66 Guan et al [28] 0.62-1.85 Brooks et al [29] 0.05-0.3 120-1450 Goel et al [30] 0.31-0.58 0.31-0.96 3-7 22-90 10-41 Ooi et al [31] 0.2-0.5 10-600 Vlachou and Karapantsios [16] 0.02-0.66 Zhou et al [33] 0.21-0.31 Ren et al [34] 0.01-0.78 Abdous et al [17] 0.53-1.67 0.82-2.4 Holagh et al [18]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Proposed correlation by Prodanovic et al [24] was modified and adapted for predicting bubbles departure diameter and nucleation frequencies in U-shaped channels through adding Dean number as a new factor, which considers the influence of the curved geometry and subsequently, radial pressure gradient on bubbles characteristics. Ghunther [19] 0.32-1.02 0.8-3 Tolubinsky and Kostanchuk [20] 0.47-1.24 1.2 Ünal [5] 0.11-0.18 Klausner et al [22] 0.1-0.65 Thorncroft et al [23] 0.09-0.25 0.12-45 1-1.8 17-30 Prodanovic et al [24] 0.3-2.68 0.37-2.86 0.41-9.5 0.81-18.6 Situ et al [42] 0.145-0.6 Cho et al [1] 0.46-0.56 0.55-0.9 Chu et al [9] 0.51-1.71 77-300 Euh et al [41] 20-900 Zou and Jones [27] 0.15-0.45 Sugrue et al [3] 0.22-0.66 Guan et al [28] 0.62-1.85 Brooks et al [29] 0.05-0.3 120-1450 Goel et al [30] 0.31-0.58 0.31-0.96 3-7 22-90 10-41 Ooi et al [31] 0.2-0.5 10-600 Vlachou and Karapantsios [16] 0.02-0.66 Zhou et al [33] 0.21-0.31 Ren et al [34] 0.01-0.78 Abdous et al [17] 0.53-1.67 0.82-2.4 Holagh et al [18]…”
Section: Discussionmentioning
confidence: 99%
“…They found that the biggest bubbles depart in the downward-facing horizontal heater configuration and the smallest bubbles from a vertically positioned heater. Guan et al [28] investigated bubbles departure diameter in water sub-cooled flow boiling at atmospheric pressure and proposed a model for departure diameter prediction. An experimental study of wall nucleation characteristics, embracing departure diameter and frequency, during subcooled flow boiling of water in a vertical straight channel was carried out by Brooks et al [29] at various working pressures.…”
Section: Introductionmentioning
confidence: 99%
“…89,90 Bubble detachment at a heat transfer surface has been extensively studied in which the bubble departure relative to a general wall is investigated. [89][90][91][92] For gas-evolving electrochemical systems, bubbles at an electrode surface are further influenced by two additional forces: the electrostatic force, F e , and the Marangoni force, F M . 86 The electrostatic interactions between the electrode surface charge and the bubble surface can cause a premature departure of the bubble from the electrode surface, or F e may oppose the direction of bubble growth retaining the bubble at the electrode surface.…”
Section: Force (N) Definitionmentioning
confidence: 99%
“…A common theme in biphilic flow boiling studies is the hastening of bubble departure through exploitation of contact line pinning and drag forces; considering a force balance on a growing bubble, there is an impetus to decrease the stiction forces and/or increase departure forces in order to enhance the sweeping of the bubbles from their nucleation sites. Recent work has connected contact-line pinning to the bubble force balance as proposed by Klausner and colleagues, , indicating that control over the bubble’s perimeter can shift the force balance in favor of departure.…”
Section: Introductionmentioning
confidence: 99%